HUBUNGAN GEJALA PENYERTA DENGAN FATIGUE PADA PASIEN KANKER PAYUDARA YANG MENJALANI KEMOTERAPI - Ellyza Fazlylawati; Nurul Amna; Khaira Rizki (Medic Nutricia : Jurnal Ilmu Kesehatan, 2024)
Background: As the most common disease to be diagnosed, breast cancer now surpasses lung cancer in frequency and disrupts a patient's life in many ways. Chemotherapy is one of the treatments that people with breast cancer receive. Patients who get this medication may encounter side effects, chief among them being weariness, which is the most prevalent issue and significantly impairs normal function in breast cancer patients. Fatigue is caused by a variety of circumstances, including its accompanying symptoms. The purpose of this research was to ascertain how fatigue and concomitant symptoms related to breast cancer patients receiving chemotherapy were related. Materials and procedures: Purposive sampling was employed to choose 153 breast cancer patients who were receiving chemotherapy for this cross-sectional study design. The Cancer Fatigue Scale and questionnaires were utilized for data collection